Indicadores de desenvolvimento humano municipal (IDHM) e desigualdades em San- tarém-PA: uma abordagem histórica dos censos de 1991, 2000 e 2010 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study aims to analyze the evolution of the Municipal Human Development Index (MHDI) in Santarém-PA, based on data from the Demographic Censuses of 1991, 2000, and 2010, in order to understand the historical dynamics of socioeconomic inequalities in the municipality. To investigate this theme, the following research questions were adopted: How did the MHDI indicators reflect the social and economic transformations in Santarém-PA between the 1991, 2000, and 2010 censuses? And in what way do these data reveal the persistence or overcoming of inequalities in the municipality during this period? To address these questions and achieve the proposed objectives, it was necessary to adopt, as a theoretical instrument, a discussion on the concepts of development and economic growth in light of economic theory and authors who examine these issues in the Latin American context. From a methodological perspective that seeks to connect theory and practice, we adopted an applied and investigative research approach, using secondary data calculated by UNDP, FJP, and IPEA (2013) related to the MHDI and its components—income, education, and longevity—for the census years of 1991, 2000, and 2010. These data were complemented by social statistics obtained from secondary sources, aiming to enhance the interpretation of these indicators. The results showed that all human development indicators were classified as low or very low at the beginning of the series; however, the longevity index showed a rising trend throughout the analyzed years. The association between GDP growth data and those measuring quality of life and access to basic services did not move in the same direction, thus revealing income concentration, low quality of life, unequal distribution of basic sanitation services, and social exclusion.
Keywords: IDHM; desenvolvimento; crescimento econômico; desenvolvimento humano; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS